Niveles de comprensión lectora según género en estudiantes de sexto grado de primaria de una I.E. del Callao - Luque Mamani, Carmen Rosa (2010)
The purpose of the research is to determine the levels of the reading comprehension in boys and girls from sixth grade of a primary school from Callao. For this research it has been used the descriptive method. The sample, according to the no probabilistic criterion was formed by 42 boys and 42 girls, which were evaluated with the test of reading comprehension ACL6 created by Gloria Catala, Mireia Catala, Encarna Molina and Rosa Monclus, adapted by Ortega and Ramirez(2010). Taking into consideration the global performance, it was observed that a 54% of the students showed a low level of reading comprehension. To compare the differences between genre, it was used the statistics of Mann-Whitney. The obtained results showed that the boys present better levels of reorganization, inference and criteria of reading comprehension in front of the girls; in the literal level it was not observed differences between genres.